The Authority of the Local Government in Forest Management and its Implication toward Local Autonomy in Riau Province - Gusliana HB (Faculty of Law, Jambi University, 2018)
The authority of local government in forest management in the Province of Riau has not been running as yet so far, because there is deviation in it, that caused by functionaries as well as individual community around of the forest area. Forest management by the regency government is still far from the principles of well government management, transparency, participation, accountability, and professional. The obstacles for local government to do forest management authority in the Province of Riau such as, firstly, law and regulations. Secondly, permit and supervision instruments. Thirdly, law enforcement officers. Fourthly, community. While the system of local government authority farther in forest management can be done through first, the system of forest management through Unity of Forest Management (KHP) concept. Second, the system of community participation by involving the local community more broadly in planning, maintenance, management, decision making, implementation, and supervision. In order to give comprehension for local community that importance of everlasting and sustainable forest management program for future generation by increasing counseling and socialization. The implication of forest management towards local autonomy shows a dynamic transformation, authority friction in forest management that was decentralization became centralization.